Analisis Persepsi Kepuasan Kualitas Pelayanan Transportasi Masyarakat pada Bus Trans Siginjai Dinas Perhubungan Provinsi Jambi - Pebri Nursani Sihombing; Sumarni Sumarni; Dwi Kurniawan (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
The purpose of this study is to analyze public perceptions of the quality of the Trans Siginjai Bus service provided by the Jambi Provincial Transportation Agency, and to identify and analyze factors influencing public satisfaction with the Trans Siginjai Bus transportation service in Jambi City. This study used qualitative methods with data collection techniques including observation, interviews, and documentation. Based on the research results, public assessments of the Trans Siginjai Bus in Jambi City show two opposing sides. On the one hand, they are satisfied because the bus is affordable, practical, safe, and has strategic routes, so many continue to use it and recommend it. However, on the other hand, service issues are more prominent, such as dirty and damaged buses and bus stops, frequently late schedules, unfriendly drivers, and the lack of an easy way to complain. This makes people annoyed and less loyal in the long run. Their satisfaction depends on the balance between these advantages and disadvantages such as uncomfortable facilities, uncertain schedules, inadequate staff service, and a lack of attention to complaints. So, people appreciate the economic benefits but remain disappointed with the overall service quality.